An Enhanced Secure Image Cryptography based on RC6 and RSA to Minimize Entropy and Improve Correlation (International Journal of Engineering and Computer Science, 2016)
a secure environment would not be possible without the existence of encryption technology.  Image, which covers the large percentage of the multimedia data, its protection is very important in a current scenario. So focusing the security possibility an efficient image cryptography system based on RC6 and RSA have been proposed in this paper. The specialty of this approach is the number of keys. There are four different keys are needed for decryption process along with the extra shifting of pixels by XOR.  The key size and number of variable rounds makes this framework more secure. The key size is variable up to 2040 bits. The results are achieved in terms of entropy and correlation coefficients. The less variation in entropy is achieved from our approach which shows the efficiency of our approach.